Kearifan Lokal Tambang Rakyat sebagai Wujud Ecoliteracy di Kabupaten Bangka - Derita Prapti Rahayu (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The issues studied in this research included, first: how to build ecoliteracy for a sustainable environment? Second, how the local wisdom in people mining as a form of ecoliteracy in Bangka is. This research used a socio-legal approach with the techniques of data collection through documentation, participative observation and interviews. The result of the research concluded that first: ecoliteracy development for a sustainable environment can be done by reviewing the local wisdom of local communities. The participation of community in protecting and preserving local wisdom is in line with Article 70 paragraph (3) letter (e) of Law No. 32 Year 2009. Second, the local wisdom of people mining in the form of ampak tin is an essential element to build ecoliteracy in Bangka. The local wisdom in people mining in the form of ampak tin needs to be strengthened in the form of regulations of local governments to prevent Bangka Regency from the threat of environmental damages. In addition, the ampak tin must be preserved and used as a form ecoliteracy in Bangka for a sustainable environment.